Pengaruh Terapi Rebusan Daun Sirsak Terhadap Penurunan Kadar Kolesterol pada Penderita Hiperkolesterolemia di Wilayah KP Tipar Tahun 2022 - Siti Aisah; Irawan Danismaya; Bambang Suryadi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Hypercholesterolemia is a disorder of cholesterol metabolism caused by cholesterol levels in the blood that exceed normal limits. Hypercholesterolemia can be caused by an unbalanced lifestyle and diet. From high cholesterol levels, therapy is needed, one of which is soursop leaf decoction therapy. Purpose: this study was to determine the therapy of soursop leaf decoction in hypercholesterolemia sufferers in the Kp.Tipar Karangtengah area, Cianjur in 2022. Methods: This type of research is quantitative with a quasy experimental approach, non-equivalent pretest-posttest with control group design. The sampling technique used is non-random sampling. The instruments used are tools and materials. Statistical test using the Wilcoxon test.Results: The study showed a p-value of 0.000 <0.005, which means that there is an effect of soursop leaf decoction therapy on hypercholesterolemic sufferers in the Kp.Tipar Karangtengah area, Cianjur in 2022. Suggestion: Based on the results of the study, it is hoped that for the Kp Tipar Region, Hegarmanah Village can provide advice to hypercholesterolemia sufferers to consume soursop leaf decoction as an alternative to drugs to lower cholesterol levels.